Improved cycle outcomes after laparoscopic ovarian diathermy in hyper-responder patients with previous ART failure. (December 2014) - Pabuccu, Recai; Pabuccu, Emre Goksan; Gursoy, Asli Yarci; Caglar, Gamze Sinem; Yilmaz, Muserref Banu; Ozdegirmenci, Ozlem
Abstract Excessive response to ovarian stimulation is common among hyper-responder patients undergoing assisted reproductive technology (ART). Cycle cancellations and severe ovarian hyperstimulation syndrome (OHSS) are all detrimental consequences observed within this cohort and several approaches have been proposed to enhance outcomes. The current study is designed to evaluate whether laparoscopic ovarian diathermy (LOD) improves ART outcomes and pregnancy rates by reducing Anti-mullerian hormone (AMH) levels in a group of patients who had a history of recurrent ART failure and high response. A total of 40 hyper-responder patients with history of previous ART failure were included. Group I consisted of 22 patients that underwent LOD prior to ART. Group II consisted of 18 patients that underwent only ART. Cycle outcomes of groups were compared. Following LOD, significant reduction in AMH levels were detected in group I (4.75 ng/mL to 2.25 ng/mL). Clinical pregnancies were similar among groups (40% versus 27.8% p = 0.65). There was no cycle cancellation in Group I, whereas there were three cycle cancellations observed due to OHSS in Group II. Our results indicate that LOD might offer enhanced fertility outcomes and may reduce the likelihood of cycle cancellations in hyper-responders with previous ART failures.